The blue pixel guide to travel photography : perfect photos every time - Schloss, David (Peachpit, 2005)
When it comes to learning how to take great travel photographs, who better to learn from than the pros whose work graces the pages of all those travel magazines and brochures you & rsquo;ve examined longingly? These are exactly who you get as instructors when you purchase this book & ndash;the world-famous photojournalists, commercial and fine-art photographers, and trainers who make up the Blue Pixel team (which instructs thousands of students annually through the highly respected Nikon School of Photography). Drawing on years of in-the-trenches experience, the Blue Pixel authors outline everything you need to know to take great travel shots using the digital tools available today. Offering clear, concise instruction plus practical advice, real-world examples and anecdotes, and loads of beautiful photos, this beautiful full-color guide offers everything you need to get the right shot every time. From what equipment to buy to how to set up the perfect shot (plus more advanced topics like lighting and composition), you & rsquo;ll learn how to capture the magic of locales both local and exotic.